Electronic Dictionary Research Corpus - Sun, Wei (Journal of physics. Conference series, 2021)
The development of computer and Internet technology, and the emergence of new technologies such as electronic dictionaries and corpora have made it more convenient, accurate and reliable for students to learn to access materials. Students must master these new technologies in their study and life. The purpose of this article is to focus on the research and analysis of the electronic dictionary corpus, and to understand the influence of the electronic dictionary corpus on students’ study and life. The inquiry method used in this article is to conduct a questionnaire survey on students using the electronic dictionary corpus and then analyze the data obtained through big data technology. At the same time, this article still uses the simulation method to predict the future development prospects of the electronic dictionary corpus with the computer simulation experiment. The electronic dictionary corpus uses a variety of algorithms to query massive databases, and finally can display the data we need in front of us at the fastest speed. The dynamic BP network is used to predict the generalized predictive control prediction error. The dynamic BP network the weight can be adjusted online, which changes the situation that the traditional BP network performs error correction once the network weight is fixed after training. The experimental results show that this article conducted interviews and questionnaire surveys with experimental students and found that more than 90% of the students believe that the electronic dictionary corpus has a positive impact on students’ learning and development.